Case of surgical treatment of ascending aorta and aortic arch aneurysm in a patient with unclassified connective tissue disease - B.M. Todurov; A.Y. Shkandala; O.V. Zelenchuk; M.F. Rotar; N.S. Gnoyanko (Кардіохірургія та інтервенційна кардіологія)
Thoracic aortic aneurysm is one of the most serious pathologies of the cardiovascular system. Survival of patients without surgery within 5–10 years does not exceed 13–19 %. Prevalence of thoracic aortic aneurysms is steadily increasing and is now about 10.4 per 100,000 population per year. The risk of sudden death is extremely high. The only way to save a patient's life is through surgical treatment. Only early diagnosis and timely reconstructive surgery are able to reduce the percentage of complications and reduce mortality in this pathology. The article presents clinical case of ascending aorta and aortic arch aneurysm in a patient with unclassified hereditary connective tissue disorder, with successful surgical treatment. The difficulties of phenotypic diagnosis of hereditary syndromes and the importance of timely identification of stigmas of dysbiogenesis are demonstrated. The very fact of detecting an aneurysm of the thoracic aorta requires careful phenotypic examination and search for genetically determined pathology. The results of the phenotypic study confirm the hereditary nature of the detected pathology. The presented case demonstrates possibility of the development of thoracic aorta aneurysm in patients with unclassified connective tissue disorder with Marfan-like phenotype, but also in a number of hereditary syndromes.